2022
DOI: 10.4103/njms.njms_357_21
|View full text |Cite
|
Sign up to set email alerts
|

Piezo-osteotomy in orthognathic surgery: A comparative clinical study

Abstract: Background: After the clinical introduction of ultrasound scalpel in recent years, piezosurgery has become competitive with conventional instruments in orthognathic procedures to reduce the operative and postoperative complications reported to occur in association with these surgeries. Aims: The aim of this prospective clinical study was to compare intraoperative and postoperative outcomes of both piezoelectric device and the traditional bur technique in orthognathic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…In our study, piezotome was used for osteotomies due to its meticulous advantages which include, reduced nerve affection, enhanced visibility of surgical field and accurate bone cutting. This runs in parallel with Harshitha Raj (2022) (28). It provides smooth cutting due to its cavitation effect.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, piezotome was used for osteotomies due to its meticulous advantages which include, reduced nerve affection, enhanced visibility of surgical field and accurate bone cutting. This runs in parallel with Harshitha Raj (2022) (28). It provides smooth cutting due to its cavitation effect.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Concerning the duration of surgery and postoperative hospital stay, MITs often demonstrate shorter operative times and reduced hospital stays owing to their precise execution and decreased surgical trauma. [ 27 28 29 ] Finally, when examining long-term outcomes and stability, both approaches exhibit comparable results, with MIT showcasing potential benefits in maintaining postoperative stability due to their tailored, patient-specific planning. [ 30 ]…”
Section: Omparison With T Raditional O ...mentioning
confidence: 99%
“…Several studies have also examined the utility of piezoelectric surgery in orthognathic surgery, where it is used to create precise osteotomies with minimal harm to adjacent structures [37][38][39]. Piezosurgery is most often used in bilateral sagittal split osteotomies, during which the inferior alveolar nerve bundle is at risk for injury.…”
Section: Orthognathic Surgerymentioning
confidence: 99%
“…Similar to other procedures, the main concerns with implementing piezosurgical techniques center on longer osteotomy and overall operative times, particularly in the context of having to cut through more dense cortical bone during orthognathic procedures. Studies have demonstrated mixed results with these outcomes, finding either longer [37,48,49], shorter [39], or equivalent [52] osteotomy or operative times.…”
Section: Orthognathic Surgerymentioning
confidence: 99%
See 1 more Smart Citation